SISTEM INFORMASI PENJADWALAN TERAPI KLINIK BERBASIS WEBSITE DENGAN NOTIFIKASI SMS GATEWAY DAN MEDIA SOSIAL - Weri Sirait; Amuharnis; Amarnis Sari, Siska (Ninety Media Publisher, 2024)
System information of scheduling theraphy is a system designed to beable to know and manage the schedule of therapy activities at My LovelyChild Clinic (MLC) Padang. At the MLC Clinic there are 5 types of therapy, where each patient therapy not only follow one type of therapy, but two to three types of therapy, depending on their needs. Treatment patients should also be monitored for their development, so that every parent of the therapy patient is required to know the progress of the therapy patient through the monthly therapy consultation. This cause we need a System Information of Scheduling Theraphy WEB Based to facilitate the scheduling of such activities and SMS Gateway based timetable reminder systems. Development of this system using PHP programming language and to build SMS Gateway application required Web Service, while for storage database using MySQL. The method used in this research is action research. Data were collected from several research subjects such as the parents of the therapy patients, as well as the admin as the patient therapy schedule regulator. Data was collected through in-depth interviews and field observations. The end result of this research is the creation of System Information of Scheduling Theraphy WEB Based with SMS Gateway Notification and Sosial Media that can facilitate the scheduling and expedite therapy activities at My Lovely Padang's clinic.